If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = -53 + -7x Reorder the terms: 7 + 5x = -53 + -7x Solving 7 + 5x = -53 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 7 + 5x + 7x = -53 + -7x + 7x Combine like terms: 5x + 7x = 12x 7 + 12x = -53 + -7x + 7x Combine like terms: -7x + 7x = 0 7 + 12x = -53 + 0 7 + 12x = -53 Add '-7' to each side of the equation. 7 + -7 + 12x = -53 + -7 Combine like terms: 7 + -7 = 0 0 + 12x = -53 + -7 12x = -53 + -7 Combine like terms: -53 + -7 = -60 12x = -60 Divide each side by '12'. x = -5 Simplifying x = -5
| -4=8+6p | | =8wx*4w | | 5x+4=2x+6 | | 7x-3=5x+4 | | 96=x+(x*2)+2*(x*2) | | x^2+9x-16=0 | | 3x-8=5x+4 | | 6(2x-3)=42 | | 4Y+16=0 | | Y+9=0 | | 2Y+15=0 | | x(4-2(2.5-x+3x))= | | 3(4x+2)=-42 | | -5x+13=-22 | | -x-6=-15 | | 12x^2+11x+c=0 | | 5x+4=2(3x-2) | | 4x-6y=6 | | -5x+5y=5 | | 10+5(z-2)=4z+1 | | 4x^4-16x^2+8x+5=0 | | 9x^2-37x+4=0 | | x^2-4x+32=0 | | 5a-3=12 | | ln(x^2+1)=60 | | 4x=140 | | 4x=139 | | -4+12=16x-3-15x | | 2a-24=a+12 | | 17x-4=12x+8 | | 15x^4-19x^2+6=0 | | 17x-4=12x+B |